Effect of growth regulator on shoot induction from protocorm of Dendrobium Anna - Anuchai, J.; Sasiangdee, A. (International Journal of Agricultural Technology, 2020)
Result showed that after 8 weeks of culture, treatment which supplemented with BA 2 mg/l was revealed to be suitable as a medium in tissue culture of Dendrobium. It showed the highest number of shoot (19.6 shoots), shoot length (1.30 cm), fresh weight (1.82 g), dry weight (0.28 g), chlorophyll A and chlorophyll B (0.19 and 0.11 mg/g FW, respectively) in treatment which supplemented with BA 2 mg/l. Total non-structural carbohydrate (TNC) showed the highest value in treatment which supplemented with NAA 0.5 and BA 0 mg/l (5.54 mg/FW). Therefore, the supplemented with BA 2 mg/l enhanced shoot induction of Dendrobium from protocorm culture and recommended for commercial production.